Enhancing total phenolic, flavonoid, and antioxidant capacity in black orchid (Coelogyne pandurata Lindl.) with paclobutrazol application - Heriansyah Pebra; Aziz Sandra Arifin; Sukma Dewi; Nurcholis Waras (BIO Web of Conferences)
The Black Orchid (Coelogyne pandurata Lindl.) is a species with promising secondary metabolite content, including total phenolics, total flavonoids, and antioxidant capacity, making it highly valuable for horticultural applications. This research investigated the influence of Paclobutrazol application on the total phenolic content, total flavonoid content, and antioxidant capacity of Black Orchid. The study was conducted using a randomized complete block design (RCBD) with Paclobutrazol treatments at concentrations of 0, 50, 100, and 150 ppm. Each experimental unit was conducted with three replicates. The data were analyzed using ANOVA, followed by Tukey’s HSD test at a 5% significance level to compare treatment means. Total phenolic, flavonoid, and antioxidant capacities were analysed using a Nano-spectrophotometer. Results indicated that treatment with 150 ppm Paclobutrazol significantly increased the flavonoid concentration in the leaves, showing a significant difference compared to the control. However, no significant effect was observed on the total phenolic content or antioxidant activity in either the leaves or bulbs.